2014
DOI: 10.2478/rjdnmd-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Metabolic Characteristics of Patients with Type 2 Diabetes Mellitus and Hypochromia

Abstract: Background and Aims. Previous studies have shown that hypochromia is a common finding in patients with chronic diseases. The aim of our study was to estimate the anthropometric and metabolic characteristics of patients with type 2 diabetes mellitus (T2DM) and hypochromia. Material and Methods. 30 patients with T2DM were recruited for this study. Patient demographics, relevant concomitant illnesses and medical history were recorded. Anthropometric, biochemical parameters (fasting plasma glucose - FPG, glycated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(5 reference statements)
2
1
0
Order By: Relevance
“…Therefore, our further investigations focused on the morphological changes and altered oxidative status of RBCs, since RBCs play an important role in microcirculation and they are vulnerable to a hyperglycemic environment. We found that the diameter of RBCs increased and abnormally shaped RBCs occurred more often in diabetics compared to controls, in line with other studies [11,34]. We observed eccentrocytes, hemolyzed RBCs, and codocytes in larger proportions in diabetic smears.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, our further investigations focused on the morphological changes and altered oxidative status of RBCs, since RBCs play an important role in microcirculation and they are vulnerable to a hyperglycemic environment. We found that the diameter of RBCs increased and abnormally shaped RBCs occurred more often in diabetics compared to controls, in line with other studies [11,34]. We observed eccentrocytes, hemolyzed RBCs, and codocytes in larger proportions in diabetic smears.…”
Section: Discussionsupporting
confidence: 92%
“…Increased hemolysis was described in the pathomechanism of some oxidative-stress-related diseases, such as diabetes mellitus, sepsis, or sickle cell disease [19,[39][40][41]. Codocytes also occur in diseases accompanied by oxidative stress, such as diabetes mellitus, beta-thalassemia, or autism spectrum disorders [11,36,42]. In insulintreated diabetics, we observed that the occurrence of eccentrocytes and hemolyzed RBCs was similar to that of controls.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation